The use of sperm whale ivory in Chalcolithic Portugal ... : استخدام عاج حوت العنبر في البرتغال النحاسية ... - Thomas X. Schuhmacher; Arun K. Banerjee; Willi Dindorf; Chaturvedula S. Sastri; Thierry Sauvage (OpenAlex, 2013)
Skallagrim was also a great shipwright.There was plenty of driftwood to be had west of Myrar, so he built and ran another farm at Alftaness and from there his men went out fishing and seal-hunting, and collecting the eggs of wild fowl, for there was ... : كان Skallagrim أيضًا ملاحًا عظيمًا. كان هناك الكثير من الأخشاب الطافية التي يمكن العثور عليها غرب ميرار، لذلك قام ببناء وإدارة مزرعة أخرى في Alftaness ومن هناك خرج رجاله للصيد وصيد الفقمة، وجمع بيض الطيور البرية، لأنه كان هناك ...